Literature Study On The Effect of The Discovery Learning Approach On Students' Computational Thinking Ability By Considering Gender Aspects - Mendrofa, Netti Kariani; Surya, Edi; Syahputra, Edi; Sinaga, Bornok; Gultom, Syawal (Universitas Wiralodra, 2024)
This research aims to explore the findings of previous studies regarding the effect of the discovery approach on students' computational thinking ability, taking into account gender aspects. Computational thinking ability is an essential skill in today's digital era, and the appropriate learning approach can help students develop neko77 this ability. The method used in this research is a literature study by analyzing relevant journal articles and research to identify emerging findings and patterns. The research results are expected to provide valuable insights for education practitioners in designing effective and inclusive learning strategies to improve students' computational thinking abilities, considering gender differences.